Effectiveness of health-belief model-based intervention in improving knowledge, practices and awareness in utilizing a handheld-ultrasound-prototype among females with breast lumps - Ibraheem, Shahad Abdulwahhab (2022)
Breast cancer is the most common malignancy among Malaysian women. Females who tested positive for a lump on the Center of Diagnostic Nuclear Imaging were initially randomly chosen. This study aims to assess the accuracy of Prototype Handheld Ultrasound (HHUS) performance compared to Automated Breast Ultrasound (ABUS), the gold standard, and Breast Self-Examination (BSE), as well as the effectiveness of the Health Belief Module (HBM) - based intervention modules to improve knowledge, practice, and awareness regarding breast abnormalities. On the same day, all the participants went thru both modalities and assessing the images of a breast lesion using the fifth edition BIRADS lexicon characteristics. In a single-blinded randomized control study, they were randomly allocated to the intervention and control group using a computer random number generator. The intervention group was given access to a 20- minute E-educational session. At baseline and one month after the intervention, data were obtained using precise and reliable English and Malay questionnaires. Kappas was used to evaluating the level of agreement among radiologists regarding the BI-RADS lexicon. The data were examined using the SPSS 25.0 software. After that, the differences between the group and within-group effects were assessed using McNemar’s test and chi square with P-values less than 0.05. ABUS and prototype HHUS observers found the same number of breast lesions in the 324 breasts of the 162 respondents. There was no significant difference in the mean lesion size, with a maximum mean length dimension of 0.48±0.33cm. The assessment of the lesion's shape, orientation, margin, echo pattern, posterior acoustic features, and calcification of lesions was obtained with good to excellent agreements between ABUS and HHUS observers (κ=0.70-1.0). Except for lesion orientation P=0.00, there was no difference between the ABUS and prototype HHUS. Diagnostic accuracy (99.8% and 97.7-98.9%), (99.5% and 98.0-99.0%), specificity (99.8% and 99.6-99.8%), positive predictive value (98.1% and 90.3- 96.2%), and negative predictive value (90.0% and 84.4-88.7%), and areas under the curve (0.98 and 0.83-0.92; P < 0.05) were not significantly different between ABUS and prototype HHUS observers. Participants' BSE self-report findings and the prototype HHUS had a significant positive correlation for lesion size (r = 0.62- 0.93), and this difference was significant (P 0.05). only 4 (0.6%) were malignant as confirmed by histology 1.29 ±0.95(0.6-3.6cm) and the remaining lesions, 998(99.4%), had a mean length of 0.46±0.28(0.2-2.5cm) were benign. The intervention group performed better than the control group in terms of postintervention improvements in breast self-examination (BSE) and awareness about breast cancer. In terms of secondary outcomes, there were generally statistically significant differences between the groups for the means of perceived susceptibility (P=000), benefits of BSE (P<0.001), confidence of BSE (P=0.000) and health motivation (P=0.000). There was no significant difference between the perceived seriousness and BSE barriers subscales. Health motivation, confidence and health motivation increased significantly more in the intervention group than in the control group. Over a month, a within-group analysis revealed that the mean health beliefs scores for BSE barriers (108.67 to 128.68, P<0.029), BSE confidence (91.23 to 108.69, P=0.000), and health motivation (97.99 to 109.35, P<0.005) increased in the HBM-based educational intervention group compared to the control group. According to these findings, prototype HHUS is increased sensitivity and had similar specificity compared with ABUS in the diagnosis of breast abnormalities. Additionally, ABUS has similar performance to prototype HHUS in women aged 18–59 years old. ABUS or HHUS is a suitable modality for breast cancer diagnosis.